Ultrastructural changes in the respiratory zone of the lungs in the late stages of experimental Diabetes Mellitus - Zaiats, Liubomyr; Syniak, Yaroslav; Zukow, Walery (Journal of Education, Health and Sport, 2025)
Background. Today, diabetes mellitus is one of the major challenges of modern medicine and is among the most widespread endocrine disorders. Our research aimed to study the dynamics of changes in the components of the respiratory part of the lungs in streptozotocin-induced diabetes. Materials and methods. The experiments were performed on 68 white male Wistar rats weighing 180-220 g. The animals were divided into three groups: 1 – intact (n=10); 2 - control (n=30); 3 - experimental (n=28) with a model of diabetes mellitus, which was reproduced by intraperitoneal injection of streptozotocin company "Sigma" (USA), diluted in 0.1 M citrate buffer with pH 4.5, at a rate of 60 mg/kg body weight. The control group of animals received an intraperitoneal injection with an equivalent dose of 0.1 M citrate buffer solution with a pH of 4.5. Pulmonary tissue collection for electron microscopic examination was performed under thiopental anesthesia 56, 70 and 84 days after streptozotocin injection. Pieces of lung tissue were fixed in 2.5% glutaraldehyde solution, followed by fixation in 1% osmium tetroxide solution. After dehydration, the material was poured into epon-araldite. Sections obtained on an ultramicrotome "Tesla BS-490" were studied in an electron microscope «PEM-125K». All studies were performed under sodium thiopental anesthesia at the rate of 60 mg/kg of body weight. Results. Our research showed that 56, 70 and 84 days after the modeling of streptozotocin-induced diabetes changes of a dystrophic-destructive nature were noted in alveolocytes of types I and II, and endotheliocytes of hemocapillaries. At the same time, cells with increased functional activity were determined in the components of the respiratory part of the lungs. Conclusion. Streptozotocin-induced diabetes leads to severe violations of the ultrastructural organization of components of the respiratory part of the lungs. The nature and severity of structural changes in type I, II alveolocytes, and endotheliocytes of hemocapillaries depend on the duration of diabetes.